ALAM PASAMAN BARAT DALAM LUKISAN NATURALIS - Rahmad Hidayat, Drs. Ariusmedi, M.Sn., Ir. Drs. Heldi, M.Si., Ph.D. (Universitas Negeri Padang, 2018)
The purpose of the idea of the creation of this final work is to create a naturalistpainting by expressing the beauty of nature in Pasaman Barat. With the naturalbeauty of West Pasaman can be famous and become a potential for naturalattractions.The method of creating this final paper uses five stages: preparation stage,elaboration stage, synthesis stage, concept realization stage, and completion stage and the last one is exhibition of painting that has been made. In the creation of the works, use watercolors on canvas with brushstrokes techniques and use colors that match the object. The style used is the Naturalist style.The work that is visualized about the natural beauty in West Pasaman. Bydisplaying a visual form of mountain scenery, estuaries, beaches, waterfalls andlakes. The tenth work is 1) Pantai Sasak, (2) Pantai Maligi, (3) Pantai Sikabau, (4) Muaro Binguang, (5) Air Terjun Sipagogo, (6) Air Terjun Sarasah Batang Nago, (7) Pulau Panjang, (8) Pulau Pigago, (9) Gunuang Basandiang, (10) TabekGadang.Kata kunci: Alam, Pasaman Barat, Seni Lukis Naturalis